Organizational Citizenship Behavior : Hubungan Work-life balance, Transformational leadership, Dan Organizational Justice Pada Event Organizer - Sasongko, Risnandi Dwi; Mansyur, Anwar (Business Management Journal, 2025)
This study aims to analyze the relationship between work-life balance, transformational leadership, and organizational justice on organizational citizenship behavior (OCB) in employees in the Event Organizer sector. The main focus of this study is to identify the key elements that influence OCB, as well as provide recommendations for executive office management to create a work environment that is fair, balanced, and supports positive behavior in a dynamic and stressful organization. A quantitative approach was used by distributing questionnaires via Google Forms to 150 respondents selected by simple random sampling. Data analysis was conducted using multiple linear regression through SPSS 30.0. The results show that work-life balance has a positive but insignificant effect on OCB. In contrast, transformational leadership shows a negative influence that is also insignificant. Meanwhile, organizational justice had a significant negative impact on OCB. These findings indicate that OCB behavior in the event organizer sector is more influenced by individual characteristics and workplace dynamics than formal rules or leadership styles. Therefore, management is advised to increase work flexibility, strengthen two-way communication, and build a transparent justice system to encourage employee loyalty and voluntary behavior.